化简 1.(x²—y²—2xy)—3(—x²+xy)—2(x²—5/2xy)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:51:26
化简1.(x²—y²—2xy)—3(—x²+xy)—2(x²—5/2xy)化简1.(x²—y²—2xy)—3(—x²+xy)—2(
化简 1.(x²—y²—2xy)—3(—x²+xy)—2(x²—5/2xy)
化简 1.(x²—y²—2xy)—3(—x²+xy)—2(x²—5/2xy)
化简 1.(x²—y²—2xy)—3(—x²+xy)—2(x²—5/2xy)
(x²—y²—2xy)—3(—x²+xy)—2(x²—5/2xy)
=x²-y²-2xy+3x²-3xy-2x²+5xy
=(x²+3x²2x²)-y²-(2xy+3xy-5xy)
=2x²-y²
(x²—y²—2xy)—3(—x²+xy)—2(x²—5/2xy)
=x²-y²-2xy+3x²-3xy-2x²+5xy
=2x²-y²
(X-y)2-2y2+3x2-3xy-2x2+5xy
=(X-y)2-2y2-x2+2xy
=(X-y)2-y2-x2+2xy-y2
=(X-y)2-(y2+x2-2xy)-y2
=(X-y)2-(X-y)2-y2
=-y2
原式=x²-y²-2xy+3x²-3xy-2x²+5xy
=2x²-y²